Nonlinear regression for the characterization of peristaltic pumps, an alternative in the control of biological fluids (2024)
This paper presents a modeling approach to characterize two peristaltic pumps using nonlinear regression. Accuracy tests were performed by varying the height level of the pump with respect to the vessel, and it was found to have no effect on the flow rate. Filling data was recorded for 300 ml considering the voltage applied to the pumps and the filling time. A least squares curve fitting was performed with the recorded data. The exponential model was determined to be the most accurate for the two pumps, and using a simple rule of three, the equation for each desired volume was found. Finally, filling tests were performed to compare the model data with the real data. The coefficient of determination of the model for the first pump was 0.9875 and for the second pump was 0.9956. It can be concluded that the models are accurate, which is also confirmed in the comparative filling tests, where an assertiveness of more than 99% was demonstrated in all the tests performed. It is proposed to extend the studies on the use of this mathematical method as an alternative in the non-invasive control of fluids whose instruments must be handled in a sterile manner.